Karl Barth and Karl Marx: Catatan Investigasi Awal - Daniel Sihombing (Indonesian Journal of Theology, 2017)
This article is a preliminary attempt to understand the theology of Karl Barth in its relation to the ideas of Karl Marx. Barth mentions the name of Marx many times throughout his own writings and gives some theological responses to Marx’ thoughts, in modes both appreciative and critical. Barth even once claimed that theology properly worked out would result in a promise for liberation preferable to that of Marx. In this initial phase of research, the present article surveys the mentions of Marx throughout Barth’s works. The author considers each mention in context, before sketching in general and then identifying in specific certain themes resulting from this preliminary investigation, to be explored in further research.